2020
DOI: 10.3892/ol.2020.11534
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA‑CD160 decreases the immunity of CD8+ T cells through epigenetic mechanisms in hepatitis B virus infection

Abstract: The transfer and development of chronic hepatitis B virus (HBV) infection is associated with the T cell immune response, therefore investigating the key regulators of cell immune response is needed to improve chronic HBV treatment. Blood samples from patients with chronic HBV infection were used to confirm the correlation between HBV infection stage and CD160 receptor expression levels in CD8 + T cells, the CD8 + T cells are used to research the mechanism of T cell immune response modulation, moreover, C3H/HeN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…There is limited published information on non-coding RNAs produced at the CD160 locus. One recently published study suggested that a non-coding RNA produced at the CD160 locus, termed lncRNA-CD160 functioned in an immunosuppressive manner in CD8+ T-cells of patients infected with hepatitis B virus 15 . However, it is unclear exactly which transcript this corresponds to with respect to the transcripts we identified here as differentially expressed in patients with sepsis, as we detect at least two unique CD160 long non-coding RNA transcripts induced in the whole blood during sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited published information on non-coding RNAs produced at the CD160 locus. One recently published study suggested that a non-coding RNA produced at the CD160 locus, termed lncRNA-CD160 functioned in an immunosuppressive manner in CD8+ T-cells of patients infected with hepatitis B virus 15 . However, it is unclear exactly which transcript this corresponds to with respect to the transcripts we identified here as differentially expressed in patients with sepsis, as we detect at least two unique CD160 long non-coding RNA transcripts induced in the whole blood during sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, lncRNA-CD160 acts as an immune suppressor. Indeed, knockdown of lncRNA-CD160 can block HBV infection[ 23 ].…”
Section: Lncrnas In Hbv-related Immune Responsesmentioning
confidence: 99%
“…Yang Wang et al showed that lncRNA-CD244 which is induced by CD244 + CD8 + T cell in active tuberculosis (TB) infection inhibits IFN-γ/TNF-α expression in CD8 + T cells through recruitment of EZH2 to IFNG and TNFA loci for repressive chromatin states [58]. Moreover, Jiansong Wu et al have found that lncRNA-CD160 bind to histone-modification enzyme gene histone deacetylases 11 (HDAC11) to form a complex and inhibit the function of HDAC11, which further inhibits the secretion of IFN-γ and TNF-α in in hepatitis B virus infection [59].…”
Section: Effector Functionsmentioning
confidence: 99%